(untitled) (Journal of the College of Basic Education, 2026)
Objectives: The study aimed to compare the Arab seasonal divisions with the contemporary four seasons (the Western calendar), using the astronomical calendar as a standard for comparison between the two calendars (Eastern and Western). This was done to determine the similarities and differences between the seasons in the past and present, and to determine which is more accurate. Methodology: The research was divided into two parts. The first was theoretical, presenting ancient views regarding the eastern seasons, both among the Arabs and the Persians, which were collected from ancient heritage references. As for the practical part of the research, we attempted to compare the daily and monthly temperatures of the Baghdad Climate Station for each of the western, eastern, and astronomical seasons. Results: The study concluded that the seasons (winter, spring and summer) are usually hotter in the eastern calendar, while autumn is hotter in the western calendar. It also showed that the beginning and end of the eastern seasons are close to the astronomical solstice and equinox, as the difference between the eastern and astronomical calendars is approximately one week, while the difference between the western and astronomical calendars is two weeks. When comparing the temperature averages of the seasons according to the three calendars, winter (12.6) Celsius and spring (27.5) Celsius were hotter in the astronomical calendar. As for summer (35.4) Celsius, it is hotter in the eastern calendar. Finally, autumn (24.3) Celsius is hotter in the western calendar. On the other hand, it became clear that the temperature differences between the seasons are small between the two calendars (astronomical and eastern), while the temperature differences between the seasons are large between the two calendars (astronomical and western).